Keanekaragaman, Dominansi, Daya Adaptasi dan Kehilangan Hasil Beberapa Varietas Kacang Tanah (Arachis hypogeae L.) Akibat Kompetisi Gulma Berdaun Lebar di Lahan Kering - Ngawit, I Ketut; Wangiyana, Wayan; Farida , Nihla (LPPM Universitas Mataram, 2024)
The aim of this research is to determine the weed species that play the greatest role in causing yield loss of several peanut varieties in dry land. The research was carried out on dry land owned by farmers in Pesanggrahan village, Montong Gading sub-district, East Lombok Regency, for 8 months. The research consisted of two stages, the first stage was descriptive research which aimed to observe the character of weed diversity using the basic principles of vegetation analysis, to obtain data on weed growth, population, density, frequency and dominance. Meanwhile, the second study used an experimental method, and the experiment was designed using a randomized block design, with a split plot pattern. As the main plot there are three varieties of peanuts, namely the Kidang, Gajah and Kelinci varieties. Meanwhile, the sub-plot consists of five treatments, namely weed-free plants during their growth, plants with weeds of all types of weeds during their growth, plants with weeds only from grasses, sedges and broad leaves during their growth. The results of the research show that Poaceae weeds are dominant during plant growth with quite high distribution and dominance index values, so they remain dominant during plant growth. The adaptability of the three varieties of rabbits, sheep and elephants is very low in the grass weed growing environment. The adaptability of the Elephant variety is higher than that of Rabbits and Sheep, especially in plant growing environments with sedge and broad-leaved weeds. The highest loss of crop yield occurred in the treatment of all types of weed plants and in the treatment of weed plants. Meanwhile, the lowest occurred in the treatment of broad leaf weed plants.